Pengaruh Intellectual Capital, BOPO, dan Loan to Deposit Ratio terhadap Profitabilitas BPR Kota Batam - Pujatunnisa Pujatunnisa; Erni Yanti Natalia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research investigates the impact of Intellectual Capital, operational efficiency as reflected by the Operating Expenses to Operating Income ratio (BOPO), and the Loan to Deposit Ratio (LDR) on the profitability of Rural Banks in Batam City. Profitability reflects a bank’s effectiveness in managing its assets to generate optimal returns. The study adopts a quantitative research design utilizing secondary data derived from the audited financial statements of Rural Banks officially registered with the Indonesian Financial Services Authority (OJK). The research sample comprises 14 Rural Banks observed over a ten-year period (2015–2024), yielding 140 panel data observations. Data analysis is performed using panel data regression techniques with EViews 12, following appropriate model selection procedures and classical assumption testing. The findings reveal that Intellectual Capital exerts a positive and statistically significant effect on profitability, indicating that the efficient utilization of intangible assets contributes to improved financial performance. In contrast, BOPO demonstrates a negative and significant relationship with profitability, suggesting that higher operational inefficiencies adversely affect earnings. However, the Loan to Deposit Ratio does not show a significant influence on profitability, implying that increased lending activities are not always accompanied by higher profit generation. Overall, the results highlight the critical role of Intellectual Capital development and operational efficiency enhancement in supporting the long-term profitability and sustainability of Rural Banks.